Permanent annihilation of thermally activated defects which limit the lifetime of float‐zone silicon. Issue 11 (27th June 2016) - Grant, Nicholas E.; Markevich, Vladimir P.; Mullins, Jack; Peaker, Anthony R.; Rougieux, Fiacre; Macdonald, Daniel; Murphy, John D.
Abstract : We have observed very large changes in the minority carrier lifetime when high purity float‐zone (FZ) silicon wafers are subject to heat‐treatments in the range of 200–1100 °C. Recombination centres were found to become activated upon annealing at 450–700 °C, causing significant reductions in the bulk lifetime, detrimental for high efficiency solar cells and stable high powered devices. Photoluminescence imaging of wafers annealed at 500 °C revealed concentric circular patterns, with lower lifetimes occurring in the centre, and higher lifetimes around the periphery. Deep level transient spectroscopy measurements on samples extracted from the centre of an n ‐type FZ silicon wafer annealed at 500 °C revealed a large variety of defects with activation energies ranging between 0.16–0.36 eV. Our measurements indicate that vacancy related defects are causing the severe degradation in lifetime when FZ wafers are annealed at 450–700 °C. Upon annealing FZ silicon at temperatures >800 °C, the lifetime is completely recovered, whereby the defect‐rich regions vanish and do not reappear (permanently annihilated). Our results indicate that, in general, as‐grown FZ silicon should not be assumed to be defect lean, nor can it be assumed that the bulk lifetime will remain stable during thermal processing, unless annealed at temperatures >1000 °C.